2017
DOI: 10.1039/c7ra08291f
|View full text |Cite
|
Sign up to set email alerts
|

Novel amphiphilic glucose-responsive modified starch micelles for insulin delivery

Abstract: Glucose-responsive micelles with Schiff-based was reported, which had excellent stability and biocompatibility. The release of the insulin accelerated in high glucose concentration due to the highly sensitive of glucose in physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…When the glucose concentration was 1 g/L, the size of the micelles was basically unchanged, and the insulin was released inertly. When the glucose concentration was 5 g/L, the micelles completely disintegrated, and the insulin was released rapidly (Wen et al., 2017). Tan et al.…”
Section: Stimuli‐responsive Starch‐based Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the glucose concentration was 1 g/L, the size of the micelles was basically unchanged, and the insulin was released inertly. When the glucose concentration was 5 g/L, the micelles completely disintegrated, and the insulin was released rapidly (Wen et al., 2017). Tan et al.…”
Section: Stimuli‐responsive Starch‐based Nanoparticlesmentioning
confidence: 99%
“…The [3‐(4,5‐dimethylthiazol‐2‐yl)−2,5‐diphenyl tetrazolium bromide] (MTT) assays and hemolysis studies both confirmed that the glucose‐sensitive dialdehyde starch micelles (PEG‐DAS‐APBA‐Cou) had low cytotoxic activity to A549 cells and low blood toxicity. Introducing 7‐hydroxycoumarin‐4‐acetic acid may decrease the pKa of the micelles, and the starch backbone mainly enhanced its biodegradable behavior (Wen et al., 2017). Chen et al.…”
Section: Digestibility and Toxicity Of Starch‐based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of human physiological is 7.4, and the PBA and its derivatives have a high pKa (of about 8–9) generally 28. Under normal physiological environment, PBA polymer has poor water solubility and weak glucose responsiveness 29. To reduce the pKa value of PBA, two main methods have been adopted: one is to introduce a pull electron group on the benzene ring of PBA, and the other is to introduce benzenoboric acid into the copolymer 30.…”
Section: Resultsmentioning
confidence: 99%
“…Another amphiphilic glucose-sensitive dialdehyde starch polymer containing 3-aminophenylboronic acid (APBA) as a glucose-responsive group and mPEGylated dialdehyde starch (mPEG-DAS) with hydrophobic 7-hydroxycoumarin-4-acetic acid (Cou) was synthesized by Wen et al and used for the preparation of insulin-loaded micelles by a sonication method [ 94 ]. The conjugation of Cou decreased the micellar size from 241.4 to 177.9 nm, and the C.M.C.…”
Section: Micellar Drug Delivery Systems Based On Polysaccharidesmentioning
confidence: 99%